PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF DAN KETERAMPILAN PROSES SAINS DI KELAS VII.B SMP NEGERI 10 KOTA BENGKULU - Dina Laras Sati; Rosane Medriati; Nyoman Rohadi (Kumparan Fisika, 2017)
This research is a classroom action research that aims to determine the increase oflearning activities, learning outcomes and problem solving skills of students. Subjects in this research were all students of class VII.b which amounted to 23 students. This research was conducted in four steps: planning, acting, observing, and reflecting. The results of this research indicate that student learning activity in first cycle I with average score of 25,5 (enough category), increased in cycle II to 27,5 (good category), increased in cycle III to 29,5 (good category) and increased returns tocycle IV to 32 (good category). The students' cognitive learning outcomes for the first cycle obtained an average of 62,72, increased in cycle II to 73, increased in cycle III to 78 and increased again in the cycle IV  to 81,98. students average value in cycle I is 62,20; Increased in cycle II to 72,46; Increased in cycle III to 85,50 and increased again in IV cycle to 90,94. Based on the results of research can be concluded that the application of problem based learning model can increase the learning activities, learning outcomes and problem solving skills of students.